Analysis of TPACK ability of elementary school teachers in Langsa City in compiling independent curriculum teaching modules - Shalsabila, Melsya; Jannah, Misbahul; Oviana, Wati (Jurnal Geuthèë: Penelitian Multidisiplin, 2024)
Realizing independent learning, one of its successes is largely determined by the role of the teacher in preparing lesson plans. One of them is by developing teaching modules using technology integration. The appropriate technology integration model to describe these skills or abilities is Technological Pedagogical and Content Knowledge (TPACK). TPACK is the teacher's knowledge of pedagogical content and teaching technology and how the three are combined, namely, between the teacher's skills and knowledge of learning materials, teaching pedagogical skills and integrating technology in the learning process and classroom learning. The aim of this research is to analyze the level of understanding of TPACK of elementary school teachers in Langsa City in the context of preparing teaching modules, by analyzing the quality of teaching modules prepared by teachers in the 5 schools studied. The method used in this research is descriptive method with quantitative approach. Based on the results of analyzing the ability to analyze 5 teaching modules made by teachers in 5 different schools, one school in each module, it can be concluded that the teacher's TPACK ability is quite good with a Technological Knowledge (TK) score of 41.6%, Pedagogical Knowledge (PK) of 78.1%, Content Knowledge (CK) of 86.5%, Technological Pedagogical Knowledge (TPK) of 40%, Technological Content Knowledge (TCK) of 31.6%, Pedagogical Content Knowledge (PCK) of 86.6% and TPACK of 43.3%. Information technology in learning is the main alternative for these improvements